Influence Psychoeducation to Control Self in Prevention Abuse Drugs among Junior High School Students in the District Kubung, Solok Regency in Year 2023 - Aisyah Herviana Rifka; Rosfita Rasyid; Yantri Miaputra; Amel Yanis; Rozi Sastra Purna; Husna Yetti (Indonesian Journal of Advanced Research, 2024)
Drug instances have increased in Solok Regency, with Kubung District seeing the largest increase in cases. Middle school students are a vital population because, during this formative period of personality formation, they experiment and seek validation from others, which makes more supervision necessary. The purpose of this study is to ascertain how psychoeducation about self-control can help junior high school pupils in Kubung District, Solok Regency, avoid drug misuse in 2023. With a one group pretest and posttest design and proportionate random sample of 110 respondents, This research uses the Quasi Experiment method. The analysis's findings indicated that 110 students' mean self-control scores increased from 42.51 to 48.28 after receiving psychoeducation, with a p-value of 0.025 (p-value <0.05) for the Wilcoxon test. These results show an increase in the average student pretest and post-test scores, indicating a significant influence of psychoeducation on increasing self-control in preventing drug abuse, which leads one to the conclusion that psychoeducation influences junior high school students' self-control in preventing drug abuse.